Constitutional hepatic dysfunction (Gilbert's disease), about eleven cases studied in the Hospital Obrero de Lima - León Navarro, Oswaldo (1962)
We report eleven cases of Constitutional Hepatic dysfunction (Gilbert's disease), studied at the Department of Gastroenterology of the Hospital Obrero de Lima. We place this disease in the group of non Chronicles Hemolytic jaundice due to congenital defects in bilirubin metabolism. It is noted, according to the new concepts of bilirubin metabolism, the pathogenic mechanism of this disease is related to deficient activity of glucuronyltransferase, the enzyme responsible for bilirubin conjugation with glucuronic acid.